(untitled) (Shahroud Journal of Medical Sciences, 2022)
The COVID-19 pandemic has been a serious health problem in most countries in the last few months, with every country adopting different preventive and therapeutic measures based on their specific circumstances. The epidemic began in Iran on February 19, 2020, and gradually spread across the country. The epidemic extent varies, and different preventive and therapeutic measures are taken in Iran. Shahroud and Miami Counties, covered by the Shahroud University of Medical Sciences, have experienced the highest incidence of COVID-19 in Iran. However, the epidemic is well controlled by integrating the activities of the health, treatment, and research sectors and using information technology and a proprietary software application. This model can be thus studied as a successful experience. Keywords: COVID-19, Control, Successful model, Iran